Verbes d’apparence en russe - Claire Agafonov (Corela)
Thanks to the morpho-syntactic, semantic analysis of both russians verbs vygljadet’ and vygljadet’ and of their contexts, we tried to make obvious two different mechanisms pertaining to the expression of appearance : one of them is based on the speaker’s subjective representation of the world and the other one is based on the world as perceived by the speaker.